HILBERT SPACE IN SEQUENCE SPACE l2 - Alwi, Wahidah (Matematika dan Statistika serta Aplikasinya, 2014)
The main object of the vectors are the vectors can be added together and generate a vector, and produces a number is multiplied by another vector. Any set of objects with properties like this are called "vector space". In this study aims to assess pre-Hilbert space and Hilbert space in a sequence space 2 ï¬ . Based on the purpose of the study, it was found that a vector space form a pre Hilbertspace when equipped with the inner product space. While a pre-Hilbert space is complete if every Cauchy sequence (xn) in X, convergent in X called a Hilbert space.